Pranoto Mongso as Agricultural Calendar, A Javanese Cultural Heritage in the Middle of Global Climate Change - Suntoro Wongso Atmojo (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
Pranoto mongso (from Javanese, pranåtåmångså, literally “the conditions of seasons”) is a type of agricultural calendar particularly for the purpose of farming and fishing. It is a local wisdom created by the famous poet R.Ng.Ronggowarsito to introduce time and has been practiced by the people in Java Island for thousands of years. This knowledge is presumably inherited from generation to generation from the period of Medang or Mataram Kingdom (Hinduism) in the 9th century to the period of Mataram Sultanate in the17th century as a reference in the fields of agriculture economy, administration, and defense(military). Pranoto mongso has been officially used by Sri Susuhunan Pakoeboewono VII, the King of Surakarta, since June 22, 1856. It is based on solar rotation, which is similar to the Gregorian calendar. The application of pranoto mongso in the middle of climate change remains relevant as a general guideline for anticipation. For instance, Mangsa Rendeng (DecemberFebruary) is the months of storms, rains, floods, and landslides, while Kawolu (February-March) informs farmers to be prepared for plant diseases and plagues that affect humans and animals. Pranoto mongso is still limited to once-a-year rice farming. In order to anticipate climate change, pranoto mongso,as a global seasonal approach, has to be corrected using the updates and applications of climate prediction as well as the development of site-specific (or regional), dynamic cropping pattern and calendar. Water-efficient crop varieties and cultivation patterns are highly applicable for dealing with climate change. Pranoto mongso is preserved by the Javanese people, especially in Central Java Province, as global season guidelines.